The Study Of TQM Practices By Malaysia's Private University Libraries - Md. Shariffudin, Sophia Irin (2009)
The purpose of this study was to research the perception of librarians' towards TQM practices in Malaysia's Private University Libraries. The study covered TQM in three areas which were principles, applications and awareness. All elements under these areas were analyzed accordingly. In addition, the relationship between TQM principles with each elements under TQM application and awareness were explored. The main aim of the study is to explore on how TQM practices could improve and enhance from the current practices to better practices in private university libraries of Malaysia.